Human Serine Racemase: Key Residues/Active Site Motifs and Their Relation to Enzyme Function - Graham, Danielle L.; Beio, Matthew L.; Nelson, David L.; Berkowitz, David B. (Frontiers in Molecular Biosciences, 2019)
Serine racemase (SR) was the first racemase enzyme to be identified in human biology and converts L-serine to D-serine, an important neuronal signaling molecule that serves as a co-agonist of the NMDA (N-methyl-D-aspartate) receptor. This overview describes key molecular features of the enzyme, focusing on the side chains and binding motifs that control PLP (pyridoxal phosphate) cofactor binding, as well as activity modulation through the binding of both divalent cations and ATP, the latter showing allosteric modulation. Discussed are catalytically important residues in the active site including K56 and S84, the si- and re-face bases, respectively, and R135 a residue that appears to play a critical in the binding of both negatively charged alternative substrates and inhibitors. The interesting bifurcated mechanism followed by this enzyme whereby substrate L-serine can be channeled either into D-serine (racemization pathway) or into pyruvate (β-elimination pathway) is discussed extensively, as are studies that focus on a key loop region (the so-called “triple serine loop”) the modification of which can be used to invert the normal preference of this enzyme for the latter pathway over the former. The possible cross-talk between the PLP enzymes, hSR and hCBS (human cystathionine β-synthase) is discussed, as the former produces D-serine and the latter produces H2S, both of which stimulate the NMDAR and both of which have been implicated in neuronal infarction pursuant to ischemic stroke. Efforts to gain a more complete mechanistic understanding of these PLP enzymes are expected to provide valuable insights for the development of specific small molecule modulators of these enzymes as tools to study their roles in neuronal signaling and in modulation of NMDAR function.